Factors related to progression and graduation rates for RN-to-bachelor of science in nursing programs: searching for realistic benchmarks. - Robertson S; Canary CW; Orr M; Herberg P; Rutledge DN (Journal of Professional Nursing)
Measurement and analysis of progression and graduation rates is a well-established activity in schools of nursing. Such rates are indices of program effectiveness and student success. The Commission on Collegiate Nursing Education (2008), in its recently revised Standards for Accreditation of Baccalaureate and Graduate Degree Nursing Programs, specifically dictated that graduation rates (including discussion of entry points, timeframes) be calculated for each degree program. This context affects what is considered timely progression to graduation. If progression and graduation rates are critical outcomes, then schools must fully understand their measurement as well as interpretation of results. Because no national benchmarks for nursing student progression/graduation rates exist, schools try to set expectations that are realistic yet academically sound. RN-to-bachelor of science in nursing (BSN) students are a unique cohort of baccalaureate learners who need to be understood within their own learning context. The purposes of this study were to explore issues and processes of measuring progression and graduation rates in an RN-to-BSN population and to identify factors that facilitate/hinder their successful progression to work toward establishing benchmarks for success. Using data collected from 14 California schools of nursing with RN-to-BSN programs, RN-to-BSN students were identified as generally older, married, and going to school part-time while working and juggling family responsibilities. The study found much program variation in definition of terms and measures used to report progression and graduation rates. A literature review supported the use of terms such as attrition, retention, persistence, graduation, completion, and success rates, in an overlapping and sometimes synonymous fashion. Conceptual clarity and standardization of measurements are needed to allow comparisons and setting of realistic benchmarks. One of the most important factors identified in this study is the potentially prolonged RN-to-BSN timeline to graduation. This underlines the need to look beyond standardized educational norms for graduation rates and consider the realities of 'persistence' by which these students are successful in completing their studies. It also raises the question of whether student success and program success/effectiveness are two separate measures or two separate events on one progression timeline. While clarifying our thinking about success in this population of students, the study raised many questions that warrant further research and debate. Copyright © 2010 Elsevier Inc.